Effects of outdoor activity time, screen time, and family socioeconomic status on physical health of preschool children - Zong, Bobo; Li, Lun; Cui, Yufang; Shi, Wenxia (Frontiers in Public Health, 2024)
Objective: The study aims to probe the associations between screen time, outdoor activities, and the physical health of preschoolers, offering insights to shape interventions targeting myopia and obesity prevention in children. Methods: A cross-sectional study was conducted in Guangdong Province, involving a representative sample of 23,992 preschoolers and their caregivers recruited through proportional stratified cluster sampling. Data collection utilized the Chinese Early Human Capability Index (CHeHCI, eHCi), a questionnaire on children's media use in daily family life, and Body Mass Index (BMI). Linear regression and binary logistic regression models were employed to analyze the impact of screen time and outdoor activity duration on the physical health. Results: In the high family socioeconomic status (SES) group, children had significantly less screen time compared to those in the medium and low SES groups. Outdoor activity time varied significantly based on SES, with higher SES linked to extended outdoor engagement. Additionally, children's eHCi health dimension score exhibited significant SES-related differences, showcasing higher scores for children in higher SES groups. In terms of gender differences, boys dedicated significantly more time to outdoor activities than girls, yet boys had a notably higher overweight rate. Furthermore, girls demonstrated better health outcomes based on eHCi health scores. A significant association emerged between overweight and screen time in children with high SES, indicating that prolonged screen time was linked to a higher likelihood of overweight based on BMI. Additionally, a substantial negative correlation was observed between children's eHCi health dimension score and screen time. Furthermore, children's outdoor activity time exhibited a significant positive correlation with eHCi health dimension score. Regression analysis revealed that screen time could significantly negatively predict children's physical health score, while outdoor activity time could significantly positively predict children's eHCi physical health score. Conclusions: The study highlights that family SES, age, and gender play pivotal roles in influencing preschoolers' screen time and outdoor activity duration, with family SES being particularly influential. Higher family SES correlates with reduced screen time, increased outdoor activity, and elevated health levels among children. Importantly, children's screen time negatively predicts their health status, while outdoor time positively predicts their health status.